Summer Temperature Reconstruction for the Source Area of the Northern Asian Great River Basins, Northern Mongolian Plateau Since 1190 CE and its Linkage With Inner Asian Historical Societal Changes - Chen, Feng; Chen, Youping; Davi, Nicole; Zhang, Heli (Frontiers in Earth Science, 2022)
Mid-to-high latitudes of Asia and its adjacent Arctic area are some of the most sensitive regions to climate warming in Eurasia, but spatio-temporal temperature variation over this region is still limited by a lack of long-term temperature records. Here, June-July temperature reconstructions are developed from a Larix sibirica composite chronology that presents a stable positive linkage with large-scale recorded temperatures and spans 1190-2019 CE for the source area of the Northern Asian great river Basins, northern Mongolian Plateau, Inner Asia. The warmest reconstructed period and unprecedented low summer sea ice extent in the Arctic Ocean over the past 830 years was estimated to occur in the late twentieth century (1980s–present), with a mean temperature (15.0 ℃) higher than the long-term mean (13.9 ℃) of 1190-2019 CE, which is linked with the rapid increase in global temperature. No divergent tree growth responses to recent climatic warming were found in the northern Mongolian Plateau. Temperature change of the northern Mongolian Plateau plays an important role in the interaction of climate and hydrology in mid- and high-latitude Asia. In addition, we also propose that the warm climate promoted high vegetation productivity and favored the formation of power of the nomadic tribes in the Mongolian Plateau. Our temperature reconstruction provides us with an opportunity to understand the regional effects of climate warming from multiple perspectives.